The tectono-metamorphic evolution of the Theespruit Formation in the Tjakastad Schist Belt and surrounding areas of the Barberton Greenstone Belt, South Africa - Diener, Johann F. A. (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MSc)--University of Stellenbosch, 2004.